Individuated-Basis for Rights: Tahaian Offer for the Enhancement of the Human Rights Concept - Saputra, Kurniawan Dwi; Utomo, Agus Himmawan (Journal of Islamic Thought and Civilization, 2026)
To foster human progress and freedom, human rights are proclaimed as universal standards for all. However, in practice, the partiality of human rights enforcement raises many questions about its philosophical foundations. In the Muslim world, amidst many progressive thinkers’ efforts to solve the problem of Islam’s compatibility with human rights, Taha Abdurrahman’s thought on modernity, ethics, and the self offers a new perspective in the discourse on human rights. By applying qualitative analysis, this research aimed to explore Taha Abdurrahman’s critique of human rights elaborated through his overall ideas, comparing it with Axel Honneth’s social conditions of rights. Departing from the traditional issue of the relationship between rights and obligations, Taha’s new concept of human offers significant consideration of the subjective internal role in human rights. This study argued that according to Taha’s viewpoint, for human rights to function properly, they must be built upon subjective conditions. This idea corresponds to Axel Honneth’s social context for rights. Thus, Tahaian human rights draw the context inward, nurturing a self-regulative quality that enables recognitive action. This idea could become a solid basis to address the challenges posed by akrasia (weakness of will), such as those found in drug abuse and suicide. The strengthening of self-regulative power could become an important part of a human-rights-based policy to address these issues.